CFP1 coordinates histone H3 lysine-4 trimethylation and meiotic cell cycle progression in mouse oocytes - Qian-Qian Sha (Nature Portfolio, 2018)
The transcription-independent function of trimethylation of histone H3 (H3K4me) in cell division is unclear. Here, Heng-Yu Fan and colleagues report that CFP1, a subunit of the H3K4 methyltransferase, is required for oocyte meiosis, being phosphorylated and degraded during cell cycle transition.